PROSES MANAJEMEN MUTU SEKOLAH DASAR BERBASIS RELIGI - Ali Imron (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2012)
Abstract: Process of quality management in elementary school with religion base. The purpose of this research was deeply describe process of quality management in elementary school with religion base. The research method was qualitative with a phenenomenology approach and multi-case study design on 4 elementary schools with religion base. The data collection were using in-depth interview, role-participation observation, and documentation study. Data analysis used flow model and comparative constant. Research result showed  elementary school with religion base had a good quality commitment followed up with conducting quality management. The management process began with quality planning, followed with quality control, and peaked on quality improvement.Abstrak: penelitian ini bertujuan untuk memerikan secara mendalam proses manajemen mutu di Sekolah Dasar (SD) berbasis religi. Metode penelitian adalah kualitatif, pendekatan fenomenologis, dengan rancangan studi multi kasus pada 4 SD berbasis religi. Pengumpulan data dengan wawancara mendalam, observasi peran serta dan studi dokumentasi. Teknik analisis data denga model alir dan comparative constant. Hasil penelitian menunjukkan, bahwa SD berbasis religi mempunyai komitmen mutu kuat, yang ditindaklanjuti dengan melakukan manajemen mutu., Proses menejemennya dimulai dengan perencanaan mutu, dilanjutkan dengan pengendalian mutu, dan memuncak pada peningkatan mutu.